Narrative Elicitation as Ethnography: Methodological Insights From the Examination of Children's Perspective Marking in Amdo Tibetan - Ward, Shannon M. (Frontiers in Psychology, 2021)
This paper employs a case study with Amdo Tibetan children to demonstrate the benefits of narrative elicitation for ethnographic language socialization research in under-studied languages. Primarily by examining spontaneous verbal interaction, existing language socialization research has demonstrated how salient grammatical resources shape children’s understanding of cultural belief systems pertaining to sociality and the appropriate display of emotion. However, spontaneous data do not always capture children’s full linguistic repertoires and competencies, and may therefore present a partial picture of their mastery over particular grammatical systems. One such area that remains to be studied is how children use interactional cues to build their emerging knowledge of grammatical perspective marking in Tibetan languages. This paper integrates narrative elicitation with ethnographic methods from language socialization to examine how young Amdo Tibetan children mark perspective using evidentiality, the grammatically-obligatory encoding of knowledge source, an area not frequently documented in language socialization studies. Language socialization research involved 15-months of participant observation, audio-video recording, and analysis of spontaneous interactions with children aged 1-4. This ethnographic research found that adults’ narratives highlighted local theories about the importance of compassion (Tib. rnying rje) by using grammatical evidentiality to emphasize characters’ direct experiences in the story-world. However, grammatical evidentiality was under-represented in children’s spontaneous talk. To provide further insight into children’s mastery of evidentiality in this culturally salient communicative routine, I conducted narrative elicitation tasks with seven Amdo Tibetan children, aged 2-7. By framing narrative elicitation tasks as forums for social interaction in family homes, I adapted a method traditionally used in experimentation to complement the study of naturalistic interaction. Interaction analysis of the elicited narratives found that family members positioned young children as novice narrators, leading to dialogic rather than monologic narratives. Young children co-constructed shared perspectives on narrated events, and used evidentiality in conventionalized ways by mirroring the grammatical forms of adults’ previous utterances. By adapting narrative elicitation tasks to language socialization's ethnographic methods, this paper models how qualitative researchers can locate patterns in children’s experiences of language across complementary settings of data collection, an endeavor that is particularly important to research with child speakers of under-documented languages.